Mixed connective tissue disease—enigma variations?. (16th July 2016) - Ciang, Natalia C. O.; Pereira, Nídia; Isenberg, David A.
Abstract : In 1972, Sharp et al. described a new autoimmune rheumatic disease that they called MCTD, characterized by overlapping features of SSc, SLE, PM/DM, high levels of anti-U1snRNP and low steroid requirements with good prognosis. MCTD was proposed as a distinct disease. However, soon after the original description, questions about the existence of such a syndrome as well as disputes over the features initially described began to surface. The conundrum of whether MCTD is a distinct disease entity remains controversial. We undertook a literature review, focusing on the articles reporting new data about MCTD published in the last decade, to determine whether any new observations help to answer the conundrum of MCTD. After reviewing recent data, we question whether the term MCTD is appropriately retained, preferring to use the term undifferentiated autoimmune rheumatic disease.